2019
DOI: 10.3354/esr00967
|View full text |Cite
|
Sign up to set email alerts
|

Developing low-cost tags: assessing the ecological impacts of tethered tag technology on host species

Abstract: Understanding and mitigating potential effects of tags on instrumented animals is a crucial consideration when developing new tracking techniques. Some populations of aquatic megafauna spend the majority of their lives occupying small home ranges, yet conventional finescale tracking methods generally provide a limited number of non-continuous locations, while new technology is cost prohibitive. We developed a low-cost tethered telemetry system (<185 USD tag −1 ) for short-term tracking of marine turtles in nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The tags are therefore limited to developed coastlines and certain species for short term deployments. If an animal or released tag comes within GSM range, data can be relayed provided sufficient battery power [34]. The technology has not been used on whales to our knowledge due to their short surface intervals (surface series for breathing between consecutive dives), which limit real time tracking and can result in the loss of tags in remote locations.…”
Section: Introductionmentioning
confidence: 99%
“…The tags are therefore limited to developed coastlines and certain species for short term deployments. If an animal or released tag comes within GSM range, data can be relayed provided sufficient battery power [34]. The technology has not been used on whales to our knowledge due to their short surface intervals (surface series for breathing between consecutive dives), which limit real time tracking and can result in the loss of tags in remote locations.…”
Section: Introductionmentioning
confidence: 99%
“…Foraging habitats include pre-reproductive life stages—which are the most abundant life stages in the population—along with adults of both sexes. Furthermore, foraging habitats are where green turtles spend the majority of their life: juveniles may spend 20 years or more in foraging grounds until reaching maturity, and adults reside at feeding grounds during non-breeding periods ( Seminoff, Resendiz & Nichols, 2002 ; Seminoff & Shanker, 2008 ; Senko et al, 2019 ). Thus, expanding data on foraging habitats is of utmost importance for a holistic understanding of population status ( Chaloupka et al, 2008 ; Mazaris et al, 2017 ; Wildermann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although turtles D and A had the highest MSI value (0.75 and 0.56, respectively) and exhibited the greatest travel rates (mean = 18.87 and 19.18 km days −1 respectively), they presented different migration strategies. While Turtle A remained within the release location, and then initiated a migration towards the Central North Pacific (CNP), Turtle D departed shortly after deployment further inside the GC and exhibited a high travel rate (18.87 km day −1 ) until it reached Tiburon Island where it presented the lowest travel rate of this study (1.39 km day −1 ) and remained for ~60 days, ceasing its search behaviour (Zollner & Lima, 1999; Senko et al ., 2019). Turtles B, C and E showed low MSI values (range = 0.15–0.44), indicating that they made more sinuous movements, which according to optimal search strategy (Zollner & Lima, 1999), indicates that these turtles performed search behaviour in greater measure until their arrival to the identified foraging sites.…”
Section: Discussionmentioning
confidence: 99%
“…It is among the largest for loggerheads at foraging sites in the Mexican Pacific (Ramírez-Cruz et al ., 1991; Resendiz et al ., 1998; Nichols 2002; Seminoff et al ., 2004; Peckham et al ., 2011). Due to this, and the minimum drag associated with the tags we used in this study (calculated by Jones et al ., 2014 for the tags used for olive ridley ( Lepidochelys olivacea ) and green ( Chelonia mydas ) turtles), we infer that drag caused by satellite transmitter placement was not a determinant for loggerhead movements presented here, as other studies have reported (Senko et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%